Which circulating antioxidant vitamins are confounded by socioeconomic deprivation? The MIDSPAN family study. - Dinesh Talwar; Alex McConnachie; Paul Welsh; Mark Upton; Denis O'Reilly; George Davey Smith; Graham Watt; Naveed Sattar (PLoS ONE)
Background Antioxidant vitamins are often described as having "independent" associations with risk of cancer, cardiovascular disease (CVD) and mortality. We aimed to compare to what extent a range of antioxidant vitamins and carotenoids are associated with adulthood and childhood markers of socioeconomic deprivation and to adverse lifestyle factors. Methods and findings Socioeconomic and lifestyle measures were available in 1040 men and 1298 women from the MIDSPAN Family Study (30-59 years at baseline) together with circulating levels of vitamins A, C, E, and carotenoids (alpha-carotene, beta-carotene, lutein and lycopene). Markers of socioeconomic deprivation in adulthood were consistently as strongly associated with lower vitamin C and carotenoid levels as markers of adverse lifestyle; the inverse association with overcrowding was particularly consistent (vitamin C and carotenoids range from 19.1% [95% CI 30.3-6.0] to 38.8% [49.9-25.3] lower among those in overcrowded residencies). These associations were consistent after adjusting for month, classical CVD risk factors, body mass index, physical activity, vitamin supplements, dietary fat and fibre intake. Similar, but weaker, associations were seen for childhood markers of deprivation. The association of vitamin A or E were strikingly different; several adult adverse lifestyle factors associated with higher levels of vitamin A and E, including high alcohol intake for vitamin A (9.5% [5.7-13.5]) and waist hip ratio for vitamin E (9.5% [4.8-14.4]), with the latter associations partially explained by classical risk factors, particularly cholesterol levels. Conclusions Plasma vitamin C and carotenoids have strong inverse associations with adulthood markers of social deprivation, whereas vitamin A and E appear positively related to specific adverse lifestyle factors. These findings should help researchers better contextualize blood antioxidant vitamin levels by illustrating the potential limitations associated with making causal inferences without consideration of social deprivation.